DFT-guided synthesis of N, B dual-doped porous carbon from saccharina japonica for enhanced oxygen reduction catalysis - Zhang, Junjie; Wu, Chao; Wang, Jilong; Xia, Maosong; Li, Shixin; Liu, Long; Wei, Wuguo; Peng, Xing (Frontiers in Chemistry, 2024)
Introduction The oxygen reduction reaction (ORR) is a crucial determinant of the energy transformation capacity of fuel cells. This study investigates the performance of N and B dual-doped carbon in ORR. Methods Six models using density functional theory (DFT) are developed to compare the performance of different doping strategies. A highly efficient dual-doped carbon ORR catalyst (S-850-1) is synthesized from Saccharina japonica, containing 4.54 at% N and 1.05 at% B atom. Results Electrochemical analysis reveals that S-850-1 significantly outperforms the nitrogen mono-doped carbon S-850, exhibiting a higher half-wave potential of 0.861 V and a greater limited current density of −5.60 mA cm⁻2, compared to S-850’s 0.838 V and −5.24 mA cm⁻2. Furthermore, S-850-1 surpasses the performance of 20% Pt/C, demonstrating enhanced durability and exceptional resistance to CO and methanol. The 1.40 V open circuit voltage produced by S-850-1 when integrated into a Zn-air battery can power an LED light. Discussion Both theoretical and practical evaluations validate the excellent ORR performance of nitrogen and boron dual-doped carbon, as evidenced by the agreement between the electrochemical results and DFT calculations. This work not only extends the range of ORR catalysts derived from biomass but also provides guidance on creating and producing affordable, effective catalysts that utilize natural resources.